(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2024)
In the recent years, there has been a great improvement of technology in engineering as well as medical industries. Even though the technology has increased in the medical field, the patient’s waiting time in hospitals and emergency appointments is extremely costlier nowadays. In the modern lifestyle many people are susceptible to Diabetes Mellitus (DM).The management and monitoring of DM is a challenge for the diabetic patients. This paper surveys about the various methods used in self-monitoring of blood glucose levels pervasively. The devices used for self-monitoring of glucose level are also discussed in this survey. These devices are very useful in the present busy life scenario. The major disadvantage of these devices is that they are expensive and cannot afford by all diabetic patients. An idea can proposed which involves the preparation of the kit which directly calculates the glucose level and automates with an alert message that includes the diet control,exercise control and medication control.